Analysis of Information Technology Implementation in the Audit Process and Its Impact on Audit Efficiency at the Public Accounting Firm (KAP) Adi and Deki - Reyfani Amalia; Mursalim Laekkeng; Ummu Kalsum; Edy Susanto (www.amertainstitute.com, 2025)
This study explores the implementation of information technology in the audit process and its impact on audit efficiency at the Public Accounting Firm (KAP) Adi and Deki, with a focus on the use of ATLAS. The findings reveal that the implementation of ATLAS brings significant benefits, particularly in accelerating audit data management and financial statement analysis. However, the use of this technology also faces several challenges, such as data privacy issues, system integration complexity, and the need for additional resources. Auditors also face challenges including data quality, resistance to change, and the need for specific skillsets. Moreover, data security concerns, the need for continuous technology updates, and high adoption costs are major barriers. The study also identifies changes in the audit process, such as a shift towards data-driven audits, increased reliance on data analysis, and the development of more adaptive audit techniques utilizing ATLAS. Therefore, appropriate strategies are needed to overcome these challenges and improve audit effectiveness and efficiency.